La base de données dialectales : un instrument de sauvegarde et de recherche. L’exemple corse - Marie-José Dalbera-Stefanaggi (La Bretagne Linguistique, 1998)
The Corsican Language Data Bank (BDLC), which originated in fieldwork carried out from 1975 onwards with a view to compiling a new Corsican linguistic atlas, is now presented as « multimedia », enabling data to be viewed and used in a variety of ways, as described in the article.